Caution Before Embracing Team Mentoring in Academic Medical Research Training: Recommendations from a Qualitative Study. Issue 2 (July 2021) - Mancuso, Carol A.; Berman, Jessica R.; Robbins, Laura; Paget, Stephen A.
Background : Multidisciplinary team mentoring increasingly is being advocated for biomedical research training. Before implementing a curriculum that could include team mentoring, we asked faculty about their opinions of this mentoring approach. Questions/Purposes : The goals of this study were to ask faculty about the benefits, challenges, and drawbacks of team mentoring in research training. Methods : Twenty-two experienced mentors representing all academic departments at a single institution were interviewed about perceived benefits, drawbacks, and their willingness to participate in team mentoring. Responses were analyzed with qualitative techniques using grounded theory and a comparative analytic strategy. Results : Faculty noted academic pursuits in medicine usually occur within, and not across, specialties; thus, multidisciplinary team mentoring would require coordinating diverse work schedules, additional meetings, and greater time commitments. Other challenges included ensuring breadth of expertise without redundancy, skillfully managing group dynamics, and ensuring there is one decision-maker. Potential drawbacks for mentees included reluctance to voice preferences and forge unique paths, perceived necessity to simultaneously please many mentors, and less likelihood of establishing a professional bond with any particular mentor. Conclusions : Faculty recommended caution before embracing team mentoring models. An acceptable alternative might be a hybrid model with a primary mentor at the helm and a selected group of co-mentors committed to a multidisciplinary effort. This model requires training and professional development for primary mentors.